A new species of treefrog of the genus Ptychohyla (Anura: Hylidae) from Southern Mexico - Canseco-Márquez, Luis; Aguilar-López, J. Luis; Luría-Manzano, Ricardo; Pineda, Eduardo; Caviedes-Solís, Itzue W. (Zootaxa, 2017)
We describe a new species of treefrog of the genus Ptychohyla from southern Mexico occurring to the east of the Isthmus of Tehuantepec. This new species can be distinguished from Mexican congeners by a combination of a pale pink iris and the presence of nuptial excrescences in breeding males. Including this new taxon, the number of species of Ptychohyla increases to 14, with seven of these occurring in Mexico. The new species is relatively common in pristine tropical forests, but appears to be sensitive to habitat degradation and has not been found in human modified habitats, suggesting that habitat modification is a threat for this hylid frog.